COMPARING THE FINANCIAL PERFORMANCE OF MOBILE OPERATOR COMPANIES USING ECONOMIC VALUE ADDED (EVA) AND STOCK RETURN - Tandaju, Julio Rendy (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
A company has main purpose in running the business activity. Not only maximizing the profit, but also creating value for shareholder. The financial performance could be measured as the company runs in certain period. The objective of this study is to investigate the differences in financial performance between PT. XL Axiata, Tbk and PT. Indosat, Tbk. Economic Value Added (EVA) and Stock Return could be used to measure the financial performance. EVA measures the economic profit of company during a year. Stock Return is reflected the company’s ability in maintaining their equity and returning the expected return of investor. Independent sample t-test is used as the method to test the two different independent samples. The population refers to the mobile operator companies that listed in Indonesia Stock Exchange and the financial statements of both companies from 2010 to 2012 are the samples. PT. XL Axiata, Tbk reaches its best performance and has more profit or economic value for the shareholders in 2011 of the period and creates the highest return for the investors in 2010. PT. Indosat, Tbk reaches its best performance and gain more profit or economic value for the shareholders in 2012 of the period and creates the highest return for the investors in 2010.Keywords: financial performance, economic value added (eva), stock return